Carotid Endarterectomy Benefits Patients with CKD and Symptomatic High-Grade Stenosis - Mathew, Anna (American Society of Nephrology, 2010)
Endarterectomy is generally recommended for symptomatic high-grade (70 to 99%) stenosis of the internal carotid artery, but whether this procedure is beneficial among patients with chronic kidney disease (CKD) is unknown. In this re-analysis of data from the North American Symptomatic Carotid Endarterectomy Trial, we included patients with symptomatic stenosis and either stage 3 CKD (n = 524) or preserved kidney function (n = 966; estimated GFR ≥ 60). For medically treated patients with high-grade stenosis, risk for ipsilateral stroke at 2 yr was significantly higher in patients with CKD than in those with preserved renal function (31.6 versus 19.3%; P = 0.042); carotid endarterectomy significantly reduced this risk by 82 and 51%, respectively. To prevent one ipsilateral stroke, the number needed to treat by endarterectomy was four for patients with CKD and 10 for patients with preserved renal function. Compared with patients with preserved renal function, those with CKD had similar rates of perioperative stroke and death but higher rates of cardiac events. In conclusion, patients with stage 3 CKD and symptomatic high-grade carotid stenosis gain a large benefit in stroke risk reduction after endarterectomy.